The influence of the various central metals on photophysical and photochemical properties of benzothiazole-substituted phthalocyanines - Nas, Asiye; Dilber, Gulsev; Durmuş, Mahmut; Kantekin, Halit (Pergamon-Elsevier Science Ltd, 2015)
The photophysical (fluorescence quantum yields and lifetimes, fluorescence quenching studies by 1,4-benzoquinone (BQ)) and photochemical (singlet oxygen quantum yields and photodegradation studies under light irradiation) properties of tetra-benzothiazole substituted metal-free (H2Pc, 1), lead (II) (PbPc, 2) and zinc(II) (ZnPc, 3) phthalocyanine compounds were investigated in tetrahydrofuran (THF) solution. All of these compounds did not show any aggregation and they produced good singlet oxygen (especially ZnPc). The influence of the various central metal ions (zinc, lead or without metal) on the photophysical and photochemical parameters was also investigated and compared. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Photophysical; Photochemical; Fluorescence; Singlet oxygen; Photodegradation